2020
DOI: 10.1088/1757-899x/991/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of Orange (Citrus sinensis) Essential Oils Obtained by Hydrodistillation and Solvent free Microwave Extraction

Abstract: Essential oils (EOs) have gained much media attention in recent years because of their advantages in various fields, including food preservation, pharmaceuticals, herbal medicine, and natural therapies. Phenolic components which exhibit antimicrobial activity, along with some healthy substances, are present abundantly in essential oils, hence their use to prevent bacterial growth. Oranges are amongst the world’s most popular fruits. Orange (Citrus sinensis) is widely recognized for its nutritious and medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…Based on these observations, it indicated that limonene had an influence on the antibacterial potential of EOs. is is in agreement to previous reports [16,20,[35][36][37] but in contrast to some other studies [14,31,38]. e antibacterial mechanism of citrus EOs has been described by a previous study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on these observations, it indicated that limonene had an influence on the antibacterial potential of EOs. is is in agreement to previous reports [16,20,[35][36][37] but in contrast to some other studies [14,31,38]. e antibacterial mechanism of citrus EOs has been described by a previous study.…”
Section: Discussionsupporting
confidence: 93%
“…is study firstly demonstrated the synergistic effects of CREO, CAEO, and limonene with gentamicin on clinical isolates of MRSA and MSSA. is study proposed that the antibacterial activity of the citrus EOs could attribute to their lipophilicity property and the synergy between their major monoterpene hydrocarbons, limonene, and other minor components such as linalool which has been considered to be an antibacterial agent [37]. e mode of action of EOs could be due to the diffusion and accumulation of the oil in the bacterial cell membrane and then increasing cell membrane permeability, leading to cell lysis and leakage of intracellular components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, sweet orange EO from Vietnam contained D-limonene (98.238%), beta-myrcene (1.169%) and alpha-pinene (0.548% and 0.413%) (Ngân et al, 2020). However, sweet orange EO from Uganda and Rwanda showed a total of 51 and 55 volatile chemical components, respectively.…”
Section: Antimigratory Effectmentioning
confidence: 99%
“…Due to its taste and scent, orange essential oil (OEO) is one of these essential oils that is often utilized in dairy, pharmaceutical, and cosmetic products. It is a complicated natural mixture made up of over 100 components (Aboudaou et al, 2019;Ngan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%